#TITLE_ALTERNATIVE# - SAEPUDIN (NIM 13205073), AEP
In this final project, control systems of single phase inverters connected to the grid is explained. LCL filter design method is proposed. This research completed by a method to damp oscillation in grid current use virtual damping resistors. System performance is shown by simulation use PSIM program. The simulation result shows that the control systems can synchronize output voltage of inverter with grid voltage, proposed LCL filter design fulfill harmonic attenuation standard, and virtual damping resistor can attenuate oscillation in grid current.